Yannic_data_DRYAD_RSPB-2014-0502 - Yannic, Glenn; Pellissier, Loïc; Le Corre, Maël; Dussault, Christian; Bernatchez, Louis; Côté, Steeve D. (Dryad Digital Repository, 2014)
Introductory information: Caribou (Rangifer tarandus) capture and genotype data. Please contact either Glenn Yannic (glenn-dot-yannic-at-gmail-dot-com) or Steeve D. Côté (Steeve-dot-Cote-at-bio-dot-ulaval-dot-ca) with any questions of location and genotype data. Identification – lab ID (ID number used in lab), capture ID (ID number used in field), sex (male or female). Capture Location - latitude (Y) and longitude (X) coordinates (datum = WGS84) of capture. Loci - names of microsatellite loci analyzed - 16 in total, two alleles provided per loci in adjacent columns, missing data given 000.